Analisis Kesalahan Siswa dalam Menyelesaikan Soal Relasi dan Fungsi Pada Pembelajaran Mengggunakan Problem Based Learning - Kadi, Susanti; Lede, Yulius Keremata; Kerans, Geterudis (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study is to find out how mistakes made by students in solving relation and function problems in Problem Based Learning learning. The type of research used is qualitative research presented in descriptive form based on spoken and written words. The subject of the study was a grade VIII student of SMPK St. Paul Karuni. Data collection techniques used are carrying out teaching and learning activities, written tests, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, conclusion drawing. The results of this research show that there are 3 types of errors made by students, namely (1) conceptual errors, at this stage overall there are still many students who make mistakes in writing down what they know and are asked about the questions, some even don't write them down because they don't understand the questions. (2) principal errors, at this stage there are still many students making mistakes in using formulas and some write some of them down and some even don't write them at all. (3) procedural errors, all students make mistakes at this stage. This happens because students do not know the method or steps to solve the problem and make mistakes in the calculation process, so it can be concluded that the level of mathematical errors for class VIII B students at SMPK St Paulus Karuni is still very high.